Psychometric Properties of the Revised Dysexecutive Questionnaire in a Non-clinical Population - Wakely, Hannah; Radakovic, Ratko; Bateman, Andrew; Simblett, Sara; Fish, Jessica; Gracey, Fergus (Frontiers in Human Neuroscience, 2022)
Aims: The aim of this study was to assess the psychometric properties of the revised self-rated version of the Dysexecutive Questionnaire (DEX-R) within a non-clinical sample. Methods: The study was hosted online, with 140 participants completing the DEX-R, GAD-2 and PHQ-2. Sixty participants also completed the FrSBe, with 99 additionally completing the DEX-R again three weeks later. Correlations with demographic factors and symptoms of anxiety and depression were conducted. Rasch and factor analysis were also used to explore underlying subconstructs. Results: The DEX-R correlated highly with the FrSBe, indicating sound concurrent validity. Internal consistency, split-half reliability and test-retest reliability were excellent. Age and symptoms of depression and anxiety correlated with DEX-R scores, with older age associated with less dysexecutive problems. The Rasch analysis confirmed the multidimensionality of the rating scale, and a three-factor structure was found relating to activation-self-regulatory, cognitive and social-emotional processes. Frequencies of responses on DEX-R items varied, many were not fully endorsed indicating specific relevance of most but not all items to patients. Conclusion: Interpretations of DEX-R ratings of dysexecutive problems should consider mood and individual variation. Systematic comparison of DEX-R responses between healthy and clinical groups could help identify a suitable cut off for dysexecutive symptoms.